Correlation between tumor extent in radical prostatectomies and preoperative PSA, histological grade, surgical margins, and extraprostatic extension: application of a new practical method for tumor extent evaluation - Athanase Billis; Luís A. Magna; Ubirajara Ferreira (International Brazilian Journal of Urology, 2003)
PURPOSE: To evaluate a new method designed for estimating the tumor extent in radical prostatectomy specimens. The tumor extent was correlated to preoperative PSA and to several pathologic findings in the surgical specimens as well. MATERIALS AND METHODS: Tumor extent was estimated in 118 consecutive radical prostatectomies through a simple point-count method. Drawn on a sheet of paper, each quadrant of the whole mount sections contained 8 equidistant points. During the microscopic slides examination, the tumor area was drawn over the correspondent quadrant of the paper sheet. According to the extent, tumors were classified in 5 groups: 1) very limited: £ 10 positive points; 2) limited: 11-19 positive points; 3) moderately extensive: 20-35 positive points; 4) extensive: 36-39 positive points; 5) very extensive: 70 positive points. This classification was based on a previous analysis of tumor extent in 109 radical prostatectomies. The distribution was quite normal up to 69 positive points, but asymmetric above that number, including cases exceeding far above that value. We considered the quartiles of the normal distribution up to 69 positive points (groups 1 to 4), and above that value a fifth group was considered. RESULTS: There was a statistically significant and direct correlation between the tumor extent and all variables studied: preoperative PSA (p = 0.03), Gleason score (p < 0.0001), primary grade in high-grade tumors (p < 0.01), surgical margins (p < 0.0001), extraprostatic extension (pT3a) (p < 0.0001), and seminal vesicle invasion (pT3b) (p = 0.01). CONCLUSIONS: The method, which is simple and well correlated to other prognostic factors, is accessible to those pathologists working in routine pathology laboratories. Whether this method will be used by other urology centers is yet to be seen.